Perancangan Sistem Pengukuran Kinerja dengan Metode Balanced Scorecard pada Perusahaan Banija Jatu - Naufal Umar Alghifari; Budi Sulistyo; Muhammad Almaududi Pulungan (VISA: Journal of Vision and Ideas, 2024)
Banija Jatu is an individual company engaged in the herbal management industry located at Jl. Ibrahin Adjie No. 16, Indihiang, Tasikmalaya City. Currently, Banija Jatu Company is faced with an increasing number of complaints over the past five years. Meanwhile, the performance measurement that is owned only pays attention to the financial aspect and is not comprehensive to overcome these problems. Based on this, the company needs to formulate performance measurements that pay attention to financial and non-financial aspects. One of the performance measurement methods is the Balanced Scorecard which pays attention to four perspectives in the company. The design of the performance measurement itself begins by considering the internal and external conditions of the company through the SWOT method to formulate a strategy based on the company's vision and mission. From the strategy is derived into strategic goals which are then formulated Key Performance Indicator (KPI). Each level of importance is weighted on each indicator using the Analytical Hierarchy Process (AHP) method. The perspective that has the greatest weight is the customer perspective with a percentage of 48.4%. The last stage is the preparation of a performance measurement table